540-8P=120+6P

Simple and best practice solution for 540-8P=120+6P equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 540-8P=120+6P equation:


Simplifying
540 + -8P = 120 + 6P

Solving
540 + -8P = 120 + 6P

Solving for variable 'P'.

Move all terms containing P to the left, all other terms to the right.

Add '-6P' to each side of the equation.
540 + -8P + -6P = 120 + 6P + -6P

Combine like terms: -8P + -6P = -14P
540 + -14P = 120 + 6P + -6P

Combine like terms: 6P + -6P = 0
540 + -14P = 120 + 0
540 + -14P = 120

Add '-540' to each side of the equation.
540 + -540 + -14P = 120 + -540

Combine like terms: 540 + -540 = 0
0 + -14P = 120 + -540
-14P = 120 + -540

Combine like terms: 120 + -540 = -420
-14P = -420

Divide each side by '-14'.
P = 30

Simplifying
P = 30

See similar equations:

| 4(8a+-8)= | | 8z=12 | | 2x-sin(0.5x)=0 | | 7x-12=15-4x | | 8x-(x-4)=7x | | =6P+540 | | y^2-2y-35= | | 4t-2= | | x+18+4x=-10-4x-17 | | t^2-8t=19 | | 58=-8(8m+5)-3-m+8 | | -7x+3y=38 | | 2x-(x+2)=-4 | | 19-x=14 | | 2(4-7)= | | 9t-6t+t-2= | | -109+x=34+12x | | -6-13=5x+18-4x | | 78=3(x)+18 | | 12c-15=11 | | 13*2+3= | | x=2y+2z+24 | | (3-u)(2u+9)=0 | | 8-5+3-4= | | Y=3x^3-2x^2-12x+8 | | 6x+25=74 | | Y=3x^2-2x^2-12x+8 | | (2v-7)(1-v)=0 | | 22y-198x=110 | | 16p=208whatisp | | 8(x+1)+4(x+1)=6x-6 | | 0=8x^2+12x-16 |

Equations solver categories